Allometric normalization of handgrip strength in older adults: Which body size parameter is the most appropriate - Kasović, Mario; Sagat, Peter; Kalčik, Zvonimir; Štefan, Lovro; Hubinák, Andrej; Krška, Peter (BMC sports science, medicine & rehabilitation, 2023)
BACKGROUND: Although absolute handgrip strength has been associated with health-related outcomes in older adults, little evidence has been provided regarding its adjustment by a variety of body size dimensions. Therefore, the main purpose of the study was to establish the most appropriate normalization of handgrip strength by different body size parameters in a large sample of noninstitutionalized older adults. METHODS: In this cross-sectional study, we enrolled 643 men and women aged > 60, who were part of the rehabilitation center facility program. Handgrip strength was objectively measured using a Jamar Plus* + Digital Hand Dynamometer. Body size parameters included body weight and height, body mass index, waist circumference, waist-to-height ratio, fat mass and fat-free mass. The most appropriate parameter associated with handgrip strength was identified using allometry. RESULTS: Findings showed that the most appropriate body size parameter for handgrip strength normalization was height (allometric exponent: 0.85), compared to fat-free mass (0.26) and body mass (0.12). Other body size variables were not significantly associated with handgrip strength and were omitted from further analyses. The correlations between normalized handgrip strength were significant when handgrip strength was normalized by body mass and fat-free mass, while no significant correlations were found, when handgrip strength was normalized by body height. CONCLUSION: Based on the study results, body height seems to be the best body size parameter for handgrip strength normalization in older adults, omitting the influence of body size on strength performance. If handgrip strength is measured, body height may help normalize strength for large-scale research.